Blackberry banquet - Pierce, Terry (Sylvan Dell Publishing, 2008)
Forest animals enjoy the sweet, plump fruit of a wild blackberry bush. But what happens when a bear arrives to take part in the feast? Includes "For Creative Minds" section with fun facts, a recipe and information on plants and animals.